STRENGTH CHARACTERISTICS OF MORTAR CONTAINING DIFFERENT SIZES GLASS POWDER - Tamanna, N.; Norsuzailina, Mohamed Sutan; Ibrahim, Yakub; Teo, Delsye Ching Lee (UNIMAS, 2022)
A greater portion of nonrecyclable waste glass is accumulated on landfills creating a serious environmental problem. Recent studies have been carried out to utilize the waste glass in construction as partial replacement of cement. This paper investigates the fineness properties of four sizes glass particles and strength characteristics of mortar in which cement is partially replaced with glass powder in the replacement level with 10%, 20%, 30% and 40%. Mortar cubes containing with varying particle sizes in the ranges of 212 µm, 75 µm, 63-38 µm and lower than 38 µm and in a water to cement ratio 0f 0.50 and 0.45 have been prepared. Room temperature and relative humidity have been maintained 32ºC and 90% respectively during the curing process. Replacement of 10% cement with glass powder reveals the higher compressive strength at 28days than other levels of replacement. The reduction in compressive strength increases with the level of cement replacement.